Measuring the United States Balance of Payments - Kenen, Peter B. (The Review of Economics and Statistics, 1964)
T HE international transactions of the United States are larger in volume and variety than those of any other country, and the United States dollar is more widely used than any other currency. The international financial position of the United States defies simple summary, and the status of the dollar cannot be appraised by striking a single sum or balance across any set of numbers. But these familiar observations do not diminish the importance of the statisticians' efforts to devise an efficient summary. Although no one number can say very much, some summary statistics are better than others, and a proliferation of rival constructions may merely confuse a complex situtation. The balance-of-payments statistics of the United States are more complete and detailed than those of most other countries. But the Commerce Department declines to identify a surplus or deficit in the United States payments data. Instead, it spatters its tables with a dozen separate balances covering different subsets of numbers. Five of these balances, arrayed in Table 1, purport to be comprehensive, and each has been cited by one expert or another as the most appropriate measure of the